Single-cell profiling reveals IFI44L as a central regulator of immune dysregulation in high HIV viral load - Jiamin Gao; Yanjun Li; Jinping Huang; Xianzhen Huang; Qingdong Zhu; Cailing Wei; Jieling Chen; Shunda Luo; Zhouhua Xie (Medical Microbiology and Immunology, 2026)

Enzyme-immobilized hydrophilic metal-organic framework with in situ coenzyme regeneration and its application in the continuous synthesis of chiral hydroxycarboxylic acid - Danyang Zhao; Quan Yuan; Yongqi Pan; Zhao Li; Qiangqiang Xue; Yanjun Jiang; Yujun Wang; Guangsheng Luo (Chemical Engineering Journal, 2026)

A dual-functional heterosalt additive enables synergistic interphase-bulk engineering for advanced nickel-rich cathodes - Dongni Zhao; Jing Luo; Zixiang Su; Hongzeng Dou; Jingzuo He; Junwei Zhang; Yanjun Zhao; Xinfang Xu; Peng Wang; Ningshuang Zhang; Xiaoling Cui; Shiyou Li (Chemical Engineering Journal, 2026)

Antioxidant and hypoglycemic effects of phenolic-rich extracts from Eleutherococcus senticosus fruits using deep eutectic solvents - Yanjun Ren; Lizhu Zhao; Xiongfei Luo; Zhonghua Tang (Food Chemistry, 2026)

Sophaline B inhibits non-small cell lung cancer by activating NLRP3/caspase-1/GSDMD-dependent pyroptosis and PI3K/AKT/mTOR-mediated autophagy - Yibo Hou; Zhongfu Wang; Yang Wu; Ting Deng; Siyu Yang; Shaohua Ma; Yubo Zhang; Ding Luo; Yanjun Chen; Xiaoyong Dai (Natural Product Research, 2026)

The interplay of carbon, nitrogen, and phosphorus in plants: From independent effects to synergistic regulation - Yanjun Li; Chunmei Luo; Jikai Li; Jemaa Essemine; Mingnan Qu (Journal of Plant Physiology, 2026)

Improving functional and interfacial performance of whey protein by pH shift combined with enzymatic glycosylation modification and its effect on high internal phase emulsions - Luodi Xu; Peizhu Liu; Yanjun Li; Olayemi Eyituoyo Dudu; Yiping Luo; Jinju Cheng; Yujun Jiang (Innovative Food Science & Emerging Technologies, 2026)

Trianglamine-based polyurea nanofiltration membranes with exceptional acid stability and high dye/salt selectivity - Langyu Chen; Dibao Zhu; Qisheng Miao; Sisi Li; Yixuan Luo; Shiyu Liu; Weihang Jiang; Yanjun Ding; Tiefan Huang (Chemical Engineering Journal, 2026)

Characterization, in vitro digestion properties and antioxidant activity of tropical starch - gallic acid complex - Xu Wang; Jia Luo; Yuan Meng; Gang Wu; Yanjun Zhang (Food Chemistry, 2026)

Electro-trapping uranium(VI) by ternary phosphate-functionalized polymer / molybdenum disulfide / pod shell-derived biochar composite electrode - Dongqing Huang; Yun Wang; Yang Wang; Qidong Ye; Yang Li; Hao Jiang; Yanjun Du; Yan Liu; Dingzhong Yuan; Xianping Luo (Journal of Environmental Management, 2026)

Occurrence and distribution of phthalate esters in stormwater runoff and coastal water receiving bodies, Macao, South China - Yutang Luo; Tianyi Zhang; Yaru Cao; Qiying Jian; Aolei Du; Jun Yan; Yanjun Li; Youxiang Xu; Guoyuan Zhu; Xiong Xiong; Chenxi Wu; Kai Zhang (Environmental Pollution, 2026)

Corrigendum to “Surface chemistry-driven lipase activation: insights from spectroscopy and molecular simulations”. [Biores. Technol. 436 (2025) 133035] - Jihang Zhang; Siwen Ji; Jinming Zhang; Yihui Luo; Yanjun Chen; Jinglan Wu; Pengpeng Yang; Fengxia Zou; Hanjie Ying; Wei Zhuang (Bioresource Technology, 2026)

Transition from clear-water to biofloc systems improves growth, antioxidant response, and gene expression in Penaeus vannamei - Yanshuo Guo; Wenchang Liu; Yanjun Yu; Guozhi Luo; Hongxin Tan (Aquaculture, 2026)

Novel α-glucan phosphorylase coupled with thermotolerant yeast facilitated a high conversion rate from corn stover to artificial starch and microbial protein - Yanjun Li; Guoshun Xu; Jian Tian; Wangli Ji; Bo Liu; Tao Tu; Yuan Wang; Huoqing Huang; Huiying Luo; Bin Yao; Feifei Guan; Wei Zhang; et al. (Chemical Engineering Journal, 2026)

Multi-quality attributes prediction and process parameter optimization of liquid-smoked rainbow trout by different machine learning models combined with genetic algorithm - Junpeng Zeng; Jingyi Luo; Yu Song; Xiaoming Jiang; Peixu Cong; Yanjun Liu; Changhu Xue; Jie Xu (Food Research International, 2025)

Comparative study of injectable and stimuli-responsive hydrogels reinforced with cellulose nanofibers and chitosan for controlled drug delivery - Yaoting Liang; Tong Luo; Feiyun Li; Jifu Wang; Yanjun Tang (Chemical Engineering Journal, 2025)

Tannic acid-assisted construction of ZIF-8/cellulose nanofiber composite aerogels for efficient oil adsorption and oil/water separation - Wenting Huang; Yahui Tao; Ya Li; Tong Luo; Yanjun Tang (Carbohydrate Polymers, 2025)

Surface chemistry-driven lipase activation: insights from spectroscopy and molecular simulations - Jihang Zhang; Siwen Ji; Jinming Zhang; Yihui Luo; Yanjun Chen; Jinglan Wu; Pengpeng Yang; Fengxia Zou; Hanjie Ying; Wei Zhuang (Bioresource Technology, 2025)

Synergistic defense mechanisms between soybean disease resistance genes and stomatal regulation - Jikai Li; Yanjun Li; Chunmei Luo; Shubo Zhou; Jemaa Essemine; Weibo Han; Mingnan Qu (Euphytica, 2025)

Multidimensional characterization of microplastic pollution in subtropical urban soils: Combining geospatial analysis and polymer risk indexing - Aolei Du; Yanjun Li; Qiying Jian; Kai Zhang; Yutang Luo; Jun Yan; Peixin Du; Deborah M. Power; Ying Li; Yibing Ma (Journal of Hazardous Materials, 2025)

The catalytic activity of Ca/Fe-rich incineration ash in the pyrolysis of epidemic wood - Yanjun Hu; Zhenxing Luo; Long Jiao; Caimeng Yu; Jian Li; Qianqian Guo; Jian Song (Waste Disposal & Sustainable Energy, 2025)

Engineered hydrogel platform for diabetic wound healing - Jidan Cui; Jianbin Shi; Yanjun Liu; Xianbao Shi; Jin Sun; Zhonggui He; Cong Luo; Shenwu Zhang (Chemical Engineering Journal, 2025)

Multifunctional all-liquid microfluidic devices stabilized with molecular brush surfactants - Zhao Zhang; Weixiao Feng; Kaijuan Li; Jiaqiu Luo; Yunhui Wen; Yang Yang; Yanjun Lin; Shaowei Shi (Chemical Engineering Journal, 2025)

Effects of fine particulate matter bound heavy metals on intentional self-harm deaths in Guangzhou, China, insight from core chemical constituents - Chunyan Gui; Han Zhang; Zhanlu Lv; Tao Liu; Shengbing Yu; Yanjun Xu; Hualiang Lin; Jianpeng Xiao; Wenjun Ma; Bin Luo; Ling-Chuan Guo (International Journal of Biometeorology, 2025)

High-resolution mapping of grassland canopy cover in China through the integration of extensive drone imagery and satellite data - Tianyu Hu; Mengqi Cao; Xiaoxia Zhao; Xiaoqiang Liu; Zhonghua Liu; Liangyun Liu; Zhenying Huang; Shengli Tao; Zhiyao Tang; Yanpei Guo; Chengjun Ji; Chengyang Zheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Inhibition of Staphylococcus aureus biofilm by quercetin combined with antibiotics - Yanjun Ma; Xinyun Kang; Guiqin Wang; Shuangyan Luo; Xiaofeng Luo; Guilai Wang (Biofouling, 2024)

Using CO2 and oxidants for in situ regeneration of permeable reactive barriers for leachate–contaminated groundwater - Fangming Xu; Xingshen Luo; Junlong Huang; Yuecen Dong; Kaixuan Zheng; Yanting Liu; Yanjun Liu; Hongtao Wang (Journal of Environmental Sciences, 2024)

Synergetic effects during co-pyrolysis of waste textiles and Ca/Fe-rich industrial sewage sludge: Reaction kinetics and product distribution - Xu Wang; Nan Zhou; Qianqian Guo; Zhenxing Luo; Zhipeng Xia; Yanjun Hu (Waste Management, 2024)

Molecular characteristics and phylogenetic definition on the complete chloroplast genome of Petrocodon longitubus - Zaiqi Luo; FengXia Yan; Ronghui Jiang; Yanjun Chen; Changsha Luo; CongRui Li (Plant Biotechnology Reports, 2024)

National-scale Geochemical Survey: Distribution of chemical elements in stream sediment of South and Central Asia - Jun Hong; Guanglu Meng; Jing Zhang; Jifei Cao; Bin Wang; Yanjun Luo; Bo Yang; Xueqi Zhang; Domenico Cicchella (Journal of Geochemical Exploration, 2024)

Perspectives on the highly selective oxidation of copper-mediated C3N4-BiVO4 organic-inorganic hybrid catalysts and the efficient generation of reactive oxygen species - Qian Luo; Yue Chen; Yanjun Zhao; Shan He; Shirui Lv; Yuning Ma; Xintong Liu (Chemical Engineering Journal, 2024)

A multi-task learning risk assessment method for the chemical process industry - Yanjun Guo; Xinbo Ai; Wenbin Luo (Process Safety and Environmental Protection, 2024)

eDNA reveals spatial homogenization of fish diversity in a mountain river affected by a reservoir cascade - Ruli Cheng; Xinxin Zhou; Yufeng Zhang; Qinghua Li; Jiaming Zhang; Yang Luo; Qiliang Chen; Zhihao Liu; Yingwen Li; Yanjun Shen (Journal of Environmental Management, 2024)

An experimental study of mitigating coastal dune erosion by using bio-carbonization of reactive magnesia cement - Jiaming Zhang; Yuhao Li; Yi Luo; Yanjun Li; Qinggang Yang; Zijian Shen (Marine Georesources & Geotechnology, 2024)

A new method for point pollution source identification based on remote sensing inversion and water streamlines - Lan Luo; Yanjun Zhang; Wenxun Dong; Guo Zhang; Yi Xiao; Zhaohua Ge; Jinglin Zhang (Journal of Hydrology, 2024)

Application of eDNA metabarcoding for monitoring the fish diversity of the Jiangjin to Fuling section of the upper reaches of the Yangtze River - Ruli Cheng; Yang Luo; Qinghua Li; Yufeng Zhang; Zhihao Liu; Qiliang Chen; Yingwen Li; Yanjun Shen (Hydrobiologia, 2023)

Numerical study on a coaxial geothermal exchanger equipped with a new inner tube: Entropy generation, thermodynamic irreversibility analysis and exergy efficiency performance evaluation - Qiangbin Liu; Yanjun Zhang; Xin Zhang; Yuxiang Cheng; Ji Luo; Jianqiao Zheng; Yulong Liu; Junqing Lou (Journal of Cleaner Production, 2023)

Conversion and syngas production of toluene as a biomass tar model compound in chemical looping reforming - Ming Luo; Ruicong Shen; Yanjun Qin; Honglin Liu; Yiran He; Qingrui Wang; Junfeng Wang (Fuel, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Recent trends in degradation strategies of PFOA/PFOS substitutes - Zizi Li; Zhi-Mei Luo; Yanjun Huang; Jia-Wei Wang; Gangfeng Ouyang (Chemosphere, 2023)

Contribution of five major apple polyphenols in reducing peanut protein sensitization and alleviating allergencitiy of peanut by changing allergen structure - Shanfeng Sun; Tianyi Jiang; Yanjun Gu; Lu Yao; Hang Du; Jiangzuo Luo; Huilian Che (Food Research International, 2023)

The distinct fruit size and physical defense promote divergent secondary seed dispersal strategies of three oak species - Xi Chen; Yanjun Luo; Rong Wang; Fang K. Du (Forest Ecology and Management, 2023)

Impact of thermal structure of planetary boundary layer on aerosol pollution over urban regions in Northeast China - Shuo Lu; Xiaolan Li; Tianliang Zhao; Yanjun Ma; Yangfeng Wang; Yunhai Zhang; Yuehan Luo; Yushan Xin (Atmospheric Pollution Research, 2023)

Genetic Diversity of Jinshaia sinensis (Cypriniformes, Balitoridae) Distributed Upstream of the Yangtze River - Yang Luo; Yufeng Zhang; Ruli Cheng; Qinghua Li; Yu Zhang; Yingwen Li; Yanjun Shen (Fishes, 2023)
The upper reaches of the Yangtze River (upper YR) are a biological zone with extremely rich fish diversity, especially endemic fish. However, long-term human interference, such as environmental pollution and cascade hydropower construction, has significantly changed the habitat of many fish and is threatening the number and genetic diversity of fish populations. Jinshaia sinensis is a typical small and endemic but rare fish that is found in the upper YR, and its genetic diversity and structure still need further study. To understand the current levels of genetic diversity in J. sinensis, we analyzed the genetic diversity, population history, genetic structure, etc., of three J. sinensis populations based on two mitochondrial genes (the cytochrome-c oxidase subunit I, COI, and cytochrome-b gene, Cytb) and two nuclear genes (recombination-activating protein 1, RAG1, and rhodopsin, RH). The genetic diversity analysis indicated that J. sinensis had high genetic diversity, with high haplotype diversity (h) and nucleotide diversity (Pi). Population pairwise FST analysis revealed a significant genetic divergence between the Lijiang and Luzhou populations for all genes and between the Panzhihua and Luzhou populations, except for the COI gene; however, analyses of molecular variance (AMOVA) showed no significant geographic genetic structure among populations, and gene flow analysis also indicated a certain degree of gene exchange among populations. Haplotype network structure analyses revealed low levels of shared haplotypes among populations. Neutrality test and mismatch distribution results indicated that only the Lijiang population had experienced obvious population expansion. Overall, these results indicate that J. sinensis is still a single evolutionarily significant unit, but when considering the threat of habitat disturbance to the population, it is still necessary to carry out long-term genetic monitoring on J. sinensis and on other endemic fishes with similar ecological habits in order to maintain the genetic diversity of fishes in the upper YR.

What will the water quality of the Yangtze River be in the future? - Wenxun Dong; Yanjun Zhang; Liping Zhang; Wei Ma; Lan Luo (Science of The Total Environment, 2023)

Mixed heavy metals exposure affects the renal function mediated by 8-OHG: A cross-sectional study in rural residents of China - Xiaoyu Tian; Xiaobing Shan; Li Ma; Chenyang Zhang; Mei Wang; Jie Zheng; Ruoyi Lei; Li He; Jun Yan; Xun Li; Yanjun Bai; Keqin Hu; et al. (Environmental Pollution, 2023)

Farmland quality assessment using deep fully convolutional neural networks - Junxiao Wang; Xingong Li; Xiaorui Wang; Shenglu Zhou; Yanjun Luo (Environmental Monitoring and Assessment, 2023)

Interpreting the Influence of Reservoir Water Level Fluctuation on the Seepage and Stability of an Ancient Landslide in the Three Gorges Reservoir Area: A Case Study of the Outang Landslide - Zhenwei Dai; Yanjun Zhang; Chenyang Zhang; Jianhua Luo; Wang Yao (Geotechnical and Geological Engineering, 2022)

Comparison in phytoplankton diversity-productivity-community stability between river-type reservoir and lake-type reservoir - Qiong Wu; Qiuhua Li; Huan Luo; Qian Chen; Huaxiang Chen; Yanjun Dong; Shenghua Li (Journal of Oceanology and Limnology, 2022)

Mortality burden caused by diurnal temperature range: a nationwide time-series study in 364 Chinese locations - Min Cai; Jianxiong Hu; Chunliang Zhou; Zhulin Hou; Yanjun Xu; Maigeng Zhou; Yize Xiao; Biao Huang; Xiaojun Xu; Lifeng Lin; Tao Liu; Jianpeng Xiao; et al. (Stochastic Environmental Research and Risk Assessment, 2021)

The Zhacang thermal field, Qinghai Province, China: its geology, geophysics, chemistry, and conceptual model - Ling Zhou; Yanjun Zhang; Yinfei Luo; Yude Lei; Shuren Hao (Arabian Journal of Geosciences, 2021)

Growing‐season temperature and precipitation are independent drivers of global variation in xylem hydraulic conductivity - Pengcheng He; Sean M. Gleason; Ian J. Wright; Ensheng Weng; Hui Liu; Shidan Zhu; Mingzhen Lu; Qi Luo; Ronghua Li; Guilin Wu; Enrong Yan; Yanjun Song; et al. (Global Change Biology, 2020)
Stem xylem‐specific hydraulic conductivity ( K S ) represents the potential for plant water transport normalized by xylem cross section, length, and driving force. Variation in K S has implications for plant transpiration and photosynthesis, growth and survival, and also the geographic distribution of species. Clarifying the global‐scale patterns of K S and its major drivers is needed to achieve a better understanding of how plants adapt to different environmental conditions, particularly under climate change scenarios. Here, we compiled a xylem hydraulics dataset with 1,186 species‐at‐site combinations (975 woody species representing 146 families, from 199 sites worldwide), and investigated how K S varied with climatic variables, plant functional types, and biomes. Growing‐season temperature and growing‐season precipitation drove global variation in K S independently. Both the mean and the variation in K S were highest in the warm and wet tropical regions, and lower in cold and dry regions, such as tundra and desert biomes. Our results suggest that future warming and redistribution of seasonal precipitation may have a significant impact on species functional diversity, and is likely to be particularly important in regions becoming warmer or drier, such as high latitudes. This highlights an important role for K S in predicting shifts in community composition in the face of climate change.

Cloning, Expression, and Bioinformatics Analysis of Heavy Metal Resistance Gene afe_1862 from Acidithiobacillus ferrooxidans L1 in Escherichia coli - Feifan Leng; Yuanli Li; Wen Luo; Qingwei Wei; Yanjun Jing; Xiaoli Wang; Mingjun Yang; Yonggang Wang (Biological Trace Element Research, 2019)

Regulatory roles of introns in fungicide sensitivity of Fusarium graminearum - Yanjun Li; Shunwen Luo; Xiaojing Jia; Yuanye Zhu; Dongming Chen; Yabing Duan; Yiping Hou; Mingguo Zhou (Environmental Microbiology, 2017)
Summary Although the roles of introns have been much debated in eukaryotic organisms, none of them have been functionally characterized in Fusarium graminearum . In this study, we characterized the roles of introns in regulation of fungicide‐sensitivity of F. graminearum . β 2 tub , cyp51A and myosin‐5 are important target genes of benzimidazoles, triazoles and cyanoacrylates respectively. To explore the sensitivity regulation functions of introns in target genes, several detailed deletion studies were completed on the intronic regions of β 2 tub , cyp51A and myosin‐5 . Phenotypic analyses showed that deletion of the fourth intron from β 2 tub gene (designated β 2 Δ i4 ), the sole intron from cyp51A gene ( cyp51A‐ Δ i ) and the second intron from myosin‐5 gene ( myo5‐ Δ i2 ) exhibited an increased sensitivity to corresponding fungicides. In contrast, deletion of the first or second intron from β 2 tub gene exhibited a decreased sensitivity to carbendazim. qRT‐PCR showed that the mRNA transcript levels of target genes were significantly downregulated in β 2 Δ i4 , cyp51A‐ Δ i and myo5‐ Δ i2 respectively. Meanwhile, Western blot assays revealed that the protein expression levels of β 2 tub was also dramatically reduced in β 2 Δ i4 , but accumulated in β 2 Δ i1 and β 2 Δ i2 . Overall, our results indicate that introns in target genes significantly regulate the fungicide‐sensitivity by influencing expression of the corresponding resident genes in F. graminearum .

Analysis of the spatial-temporal variation characteristics of vegetative drought and its relationship with meteorological factors in China from 1982 to 2010 - Qiu Shen; Liang Liang; Xiang Luo; Yanjun Li; Lianpeng Zhang (Environmental Monitoring and Assessment, 2017)

Soaking in H2O2 regulates ABA biosynthesis and GA catabolism in germinating cotton seeds under salt stress - Xiangqiang Kong; Zhen Luo; Yanjun Zhang; Weijiang Li; Hezhong Dong (Acta Physiologiae Plantarum, 2017)

Real-Time Cell Analysis for Monitoring Cholera Toxin-Induced Human Intestinal Epithelial Cell Response - Julian Ye; Yun Luo; Weijia Fang; Junhang Pan; Zheng Zhang; Yanjun Zhang; Zhiping Chen; Dazhi Jin (Current Microbiology, 2015)

Genome-wide transcriptional analysis of apoptosis-related genes and pathways regulated by H2AX in lung cancer A549 cells - Chengrong Lu; Min Xiong; Yuan Luo; Jing Li; Yanjun Zhang; Yaqiong Dong; Yanjun Zhu; Tianhui Niu; Zhe Wang; Lianning Duan (Apoptosis, 2013)